Crime and Punishment - Dostoevsky, Fyodor (New Delhi D. P. S. Publishing House, 2025)
Rodion Romanov itch Raskolnikov, a brilliant yet conflicted student lives in a rented room of a run-down apartment in St. Petersburg. Extremely handsome, proud and intelligent, Raskolnikov devises a peculiar theory about? intelligent? men being above law. To execute his theory, he contemplates committing a crime. He murders a cynical and an unscrupulous pawnbroker named Alyona Ivanovna and her sister Lizaveta. The act compels Raskolnikov to negotiate and reconcile with his own moral dilemmas.
Keywords: Novel